Gadget Use and Social Interaction and Social Emotional Conditions in Preschool Children: Penggunaan Gadget dan Interaksi Sosial serta Kondisi Sosial Emosional Anak Prasekolah - Nugraheni, Sofiana Dewi; Indanah, Indanah; Karyati, Sri (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Preschool children undergo rapid social and emotional development during early childhood while simultaneously experiencing increasing exposure to digital technology. Specific Background: Gadget use has become a routine activity among preschool children and is commonly associated with variations in social interaction behavior and social-emotional conditions in both home and school environments. Knowledge Gap: Previous studies tend to examine gadget use in general populations, with limited evidence focusing on specific kindergarten settings that concurrently assess social interaction behavior and social-emotional conditions. Aims: This study aimed to examine the relationship between gadget use, social interaction behavior, and social-emotional conditions among preschool children at Aisyiyah Bustanul Athfal V Gondangmanis Kindergarten. Results: Employing a quantitative correlational design with a cross-sectional approach involving 68 preschool children, the findings indicated a significant negative relationship between gadget use and social interaction behavior (r = −0.288; p = 0.017) and a significant positive relationship between gadget use and social-emotional problems (r = 0.334; p = 0.005). Novelty: This study integrates gadget use, social interaction behavior, and social-emotional conditions within a specific kindergarten context, providing localized empirical evidence. Implications: The findings underline the importance of structured parental and teacher guidance in regulating gadget use to support healthy social interaction and social-emotional development in preschool children. Highlights • Higher gadget use was associated with lower levels of social interaction behavior• Increased gadget use corresponded with a higher occurrence of social-emotional problems• The kindergarten-based context revealed distinctive behavioral and emotional patterns Keywords Gadget Use; Social Interaction; Social Emotional Conditions; Preschool Children; Early Childhood Development